COMPARISON OF THE METABOLIC EFFECTS OF CARVEDILOL AND METОPROLOL IN HYPERTENSIVE PATIENTS WITH OVERWEIGHT AND OBESITY. THE CAMELLIA TRIAL - S. Y. Martsevich; N. P. Kutishenko; E. V. Shilova; A. D. Deev; S. A. Shalnova; R. G. Oganov; I. A. Veliganina; E. G. Volkova; Yu. E. Voskanjan; L. I. Gapon; P Ya. Dovgalevskij; V. Ya. Ermolina; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To compare two therapies based on carvedilol or metoprolol in hypertensive patients with overweight and obesity.Material and methods. 320 patients with arterial hypertension (1-2 degree) were involved in the study. 160 patients received carvedilol and 160 patients – metoprolol. Both randomized groups were comparable on the main clinical characteristics.Results. By the end of the study both systolic and diastolic blood pressure (SBP, DBP) reduced in both groups р<0,0001. There were not differences of antihypertensive effect between investigated drugs (р=0,88 for SBP and р=0,61 for DBP). By the end of the study body mass index decreased by 0,52±0,10 kg/m2 (р<0,0001) in carvedilol group and by 0,26±0,10kg/m2 (р<0,01) in metoprolol group. Carvedilol in comparison with metoprolol had more positive effects on glucose (р<0,01) and lipid blood levels. By the end of the study urine acid blood level reduction was observed in carvedilol group (-16,6 μmol/l) while an increasing tendency - in metoprolol group. Carvedilol did not have negative effect on serum potassium and creatinine levels. Adverse effects rate was 6,3% in carvedilol group and 3,8% - in metoprolol group.Conclusion. The results of open, randomized CAMELLIA trial confirmed antihypertensive effect and good tolerability of carvedilol in common clinical practice as well as demonstrated some its advantages in patients with metabolic syndrome. Carvedilol has positive metabolic effects on lipid, glucose and uric acid levels. Carvedilol therapy is more preferable in patients with arterial hypertension and metabolic risk factors.